THE EFFECTIVENESS AND CONTRIBUTION OF ADVERTISEMENT TAX TO INCREASE THE ORIGINAL REVENUE OF MATARAM CITY - Nia Kurniati (Jurnal Ekonomi Pembangunan, 2018)
This study aims to determine the effectiveness and contribution of advertisement tax revenue to increase the realization of Mataram City's Local Revenue, and to find out the obstacles faced in regulating advertisement taxpayers and the efforts made to increase advertisement tax revenue. The type of research used is qualitative research. The type of data used is primary data and secondary data. The analytical tool used is the effectiveness ratio, contribution ratio, and descriptive analysis. The research model used is the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results showed that 2013, 2015 and 2016 the effectiveness of advertisement tax revenue was in the very effective category. As for 2014 and 2017 are in the less effective category. So that if averaged the value of effectiveness is 99.82% with the effective category. The advertisement tax contribution to the PAD is still very less because it is still in a position below 10%.